Lexicon of Madura batik: A critical discourse analysis of cultural identity representation - Rosyida Ekawati; Evi Pebri Ila Rachma (Studies in English Language and Education, 2026)
Madura batik tradition has a unique cultural brand name, luminous colors, and intricate patterns that are distinct from other batiks in Indonesia. The study of Madura batik lexicon remains limited compared to other regional batiks. This study highlights the unique contribution to both linguistic and cultural studies. The objective is to analyze how the Tanjungbumi batik lexicon reflects cultural identity and Madurese local wisdom. This study relies on qualitative data gathered through in-depth interviews with six Tanjungbumi batik craftsmen. They are all active batik artisans living or producing batik in the area. They were selected based on their active involvement over the past five years and their strong knowledge of the batik lexicon and its associated cultural meanings in local practice. From a critical discourse analysis perspective, the lexicon of Tanjungbumi batik is analyzed from the micro stage of vocabulary and related to the wider scope of society. The results of the study, in relation to the lexicon of various tools based on their functions in batik-making, fabric materials, types of dyes and wax (natural or synthetic), types of batik cloth, and motifs, represent knowledge as the expression of cultural identities and local wisdom. The lexicon of Tanjungbumi batik highlights collective narratives and conveys the harmonious relationship between Madurese people and their environment, as well as how local wisdom adapts to change with globalization and modernization, and continues to innovate while respecting its traditional roots in preserving cultural identity.